2015
DOI: 10.4014/jmb.1408.08048
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Antibodies to Varicella-Zoster Virus Using a Virus-Free Fluorescent-Antibody-to-Membrane-Antigen (FAMA) Test

Abstract: The fluorescent-antibody-to-membrane-antigen (FAMA) test is regarded as the "gold standard" to detect protective antibodies to varicella-zoster virus (VZV) because of its high sensitivity and specificity. Because the classic FAMA test uses an infectious virus for detection of antibodies to VZV, it is labor-intensive, and also requires special equipment for handling the virus. For this reason, we attempted to develop a simple and safe FAMA assay. Because VZV glycoprotein E (gE) is one of the major VZV glycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
4
0
1
Order By: Relevance
“…The reasons that varicella serology results were not analyzed were that some patients have had natural varicella infection, some patients received one versus two varicella vaccine doses (the vaccination guidelines in Québec changed while the project was ongoing), and finally there was missing information about varicella immunization or natural infection. Also, fluorescent antibody to membrane antigen is considered as the gold standard for detection of VZV antibodies in immunized individuals, yet it is currently not routinely available in Canada and could not be used for this project.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons that varicella serology results were not analyzed were that some patients have had natural varicella infection, some patients received one versus two varicella vaccine doses (the vaccination guidelines in Québec changed while the project was ongoing), and finally there was missing information about varicella immunization or natural infection. Also, fluorescent antibody to membrane antigen is considered as the gold standard for detection of VZV antibodies in immunized individuals, yet it is currently not routinely available in Canada and could not be used for this project.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the use of infectious viruses, one study has reported a simple and safer FAMA using HEK293T cells transfected with a plasmid encoding VZV glycoprotein E (gE) to replace VZV-infected cells, which is called the gE FAMA (schematic shown in Figure 1 C) [ 36 ]. The gE FAMA exhibited a similar staining effect to classic FAMA, and the gE-FAMA titers were closely correlated with the gp-ELISA data.…”
Section: Methods For the Detection Of Anti-vzv Antibodiesmentioning
confidence: 99%
“…Имеющиеся к настоящему времени тест системы для серодиагностики ВО основаны на при менении цельновирионного препарата ВВЗ или рекомбинантных аналогов гликопротеина E ВВЗ (GE) -одного из основных вирусных антигенов группы продуктов поздних генов, избирательно взаимодействующего со специфическими антите лами класса G при ВО и ОЛ [5]. В диагностических тестах применяется иммунодоминантный фрагмент белка, не содержащий эпитопов, перекрестнореа гирующих с родственными герпесвирусами [6].…”
Section: Introductionunclassified